1994
DOI: 10.1071/ea9940889
|View full text |Cite
|
Sign up to set email alerts
|

An economic assessment of rice breeding in New South Wales

Abstract: An economic assessment is made of the rice-breeding program at Yanco, New South Wales. The achievements of the breeding program over the past 30 years are identified and quantified. The economic assessment considers current investment in the breeding program and analyses the likelihood of the program achieving sufficient gains through breeding to justify that investment on economic grounds. We estimate the rate of improvement in yield and quality that would give the required increase in the industry's value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Lentil straw is an important source of fodder for livestock in Africa, South Asia and the Middle East. 1 Lentil straw has been reported to have better degradation in the rumen as compared to cereal straws. 2,3 High acceptability and digestibility of lentil straw in the ration of livestock was reported by Abbeddou et al 4 Heuzé et al 5 reported that crude protein (CP) content of lentil straw ranged between 58 and 111 g kg −1 DM and metabolisable energy (ME) ranged between 6.7 and 8.3 MJ kg −1 DM.…”
Section: Introductionmentioning
confidence: 99%
“…Lentil straw is an important source of fodder for livestock in Africa, South Asia and the Middle East. 1 Lentil straw has been reported to have better degradation in the rumen as compared to cereal straws. 2,3 High acceptability and digestibility of lentil straw in the ration of livestock was reported by Abbeddou et al 4 Heuzé et al 5 reported that crude protein (CP) content of lentil straw ranged between 58 and 111 g kg −1 DM and metabolisable energy (ME) ranged between 6.7 and 8.3 MJ kg −1 DM.…”
Section: Introductionmentioning
confidence: 99%
“…One consequence of the germplasm flows is the impact on returns to the Australian rice breeding program. If all the benefits of yield improvement are allocated to the Australian program (as in Brennan et al, 1994), the economic returns to that research will be overstated. If the impact of the international flows is taken into account, the returns to the Australian breeding efforts will be reduced by about 64%.…”
Section: Discussionmentioning
confidence: 99%
“…The rice breeding program at Y anco, first estab-lished in 1928, has been a major influence on the development of the Australian rice industry (Brennan et al, 1994). The industry has sought a number of characteristics to be incorporated in the varieties, including maturity type, high yield and various quality parameters.…”
Section: Australian Rice Industrymentioning
confidence: 99%
See 1 more Smart Citation